(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2023)
The current study aimed to identify the relationship between bullying through social media and psychological immunity, and to detect differences according to age and specialization in each of them. ) is a student of the faculties of media and sciences in the city of Damascus, and the study concluded that there is a very high level of bullying and a low level of immunity, as it was found that there is an inverse negative relationship between bullying and immunity, and the study revealed that there are differences according to age between first and last year students in bullying. In favor of first-year students and in psychological immunity in favor of last-year students. and there are differences according to the humanitarian and applied disciplines in bullying in favor of the humanitarian disciplines and in immunity in favor of applied disciplines.